Algoritmos de controle de tráfego para enxames de robôs com alvos em comum - Yuri Tavares dos Passos (2012)
Robotic Swarms are systems formed by a large number of robots, relatively simple, placed in same space and interacting among themselves to fulfill a common goal. Among the problems encountered in swarms of robots, there exists trafic control. In this problem, robots must be coordinated to avoid congestion, specicly when robots must move to same local, simultaneously. In this work, we developed three distributed algorithms for trafic control in robotic swarms, allowing to avoid congestions both on arrival at common target and leaving it. The first algorithm consists in using entry and exiting regions next to the common target. The second one consists in making a spiral-shaped queue around the target. The third one uses message comunication to drive away some robots, releasing the passage for those are next to the target. We made an analysis of each one and compare the performance of these algorithms.